Implementation Of Fully Required Elements In The Crime Of Planning Murder (Case Study In Blora State Court) - Beno Beno; Gunarto Gunarto; Sri Kusriyah Kusriyah (Jurnal Daulat Hukum, 2020)
In principle, ordinary killings are different from premeditated killings, in terms of actions that kill the lives of others, but some are carried out in a timeframe, structured and planned. In this research, the formulation of the problem formed is how is the implementation of the requirements for the fulfillment of elements in criminal acts of premeditated murder? And what are the obstacles in deciding the case of premeditated murder in the Blora State Court In the research carried out, the writing uses a sociological juridical approach, that is research that uses the method of approach to the problem by looking at the norms or laws that apply and see the implementation of the facts contained in the field. The results of the study as an answer to the formulation of the problem are (1) The element with the first plan is not a form of deliberate but in the form of how to form intentions / Opzet which has 3 conditions namely the Opzet was formed after being planned in advance, after people planned (Opzet) in advance, and planning the implementation of the "Opzet" requires a rather long period of time. (2) The obstacles of the judge in prosecuting the perpetrators of the crime of planned murder come from internal and external factors.Keywords: Fulfilled Requirements; Elements of Criminal Acts; Planned Murder.